Reforming Islamic Marriage Bureaucracy in Indonesia: Approaches and Impacts - Ahmad Tholabi Kharlie; Fathudin Fathudin; Windy Triana (Al-Jami'ah Research Centre, 2021)
This paper aims at discussing approaches to Islamic marriage administration reform in Indonesia upheld by the Ministry of Religious Affairs and the KUA. This qualitative study relies on various statutory materials to examine the reform of Islamic marriage in Indonesia. An empirical study was conducted in several KUA offices in Denpasar Bali to obtain information about reform-related regulations implementation and the approaches of the marriage administration reform made by KUAs. This paper argues that top-down policies are not sufficient to make successful bureaucratic reform. Bottom-up approaches by each KUA through solid leadership and innovation have proven to determine the success of the reform. The paper, however, found that these bottom-up approaches are not without weakness as they tend to be unsystematically taken and that not all KUAs in Indonesia, therefore, have introduced such reforms and made equal success.[Artikel ini membahas beberapa pendekatan dalam mengkaji reformasi administrasi pernikahan Islam di Indonesia yang dikelola oleh Kementerian Agama dan KUA. Studi kualitatif ini mengandalkan beberapa bukti hukum untuk menguji reformasi pernikahan Islam di Indonesia. Studi empiris ini dilakukan di sejumlah KUA di Bali untuk mendapatkan informasi mengenai implementasi kebijakan dan pendekatan reformasi administrasi yang telah dibuat KUA. Argumen dari artikel ini adalah kebijakan dari atas ke bawah tidak cukup berhasil dalam reformasi birokrasi. Sedangkan pendekatan dari bawah ke atas di masing-masing KUA melalui kepemimpinan yang solid dan inovatif, justru cenderung dominan keberhasilan reformasinya. Meskipun demikian, artikel ini juga menunjukkan kekurangannya yaitu kurang tersistematis dan tidak semua KUA di Indonesia yang juga menjalankan program reformasi dapat meraih sukses yang sama.]